Different routes the same destination: a comparative study of antitrust regulation for pharmaceutical industry in the United States and China - Weng, Jie; Liu, Nailiang (Frontiers in Pharmacology, 2025)
As a commercial trade with a public nature, the pharmaceutical industry is related to the interests of many consumers. It is important for many countries to carry out antitrust regulations in this industry, but there are differences in regulatory paths and specific practices (terms such as “anti-monopoly” and “antitrust” are used interchangeably, this study uses “antitrust” to maintain consistency in terminology). A key characteristic of the United States system is that courts play a leading role in interpreting and applying abstract antitrust laws, whereas Chinese administrative enforcement agencies directly apply specifically identified antitrust provisions for uniform regulation. Despite differences, pharmaceutical antitrust regulations in both countries ultimately aim to protect consumer welfare. This study examines the timelines of pharmaceutical antitrust regulation, the fields of regulation, the types of monopoly behavior and behavioral performances in two countries, and further analyses the differences in the regulatory paths and means, as well as the similarities and differences in the effects of regulation, in comparison with the current state of pharmaceutical antitrust regulation in the United States and China. The analysis serves as a valuable reference for the future development of pharmaceutical antitrust regulation in China.